2020
DOI: 10.1111/pce.13879
|View full text |Cite
|
Sign up to set email alerts
|

Role of melatonin in UV‐B signaling pathway and UV‐B stress resistance in Arabidopsis thaliana

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) plays important roles in plant defences against a variety of biotic and abiotic stresses, including UV-B stress. Molecular mechanisms underlying functions of melatonin in plant UV-B responses are poorly understood. Here, we show that melatonin effect on molecular signalling pathways, physiological changes and UV-B stress resistance in Arabidopsis. Both exogenous and endogenous melatonin affected expression of UV-B signal transduction pathway genes. Experiments using UV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 67 publications
(92 reference statements)
0
28
0
Order By: Relevance
“…The function of melatonin in plants has been widely reported ( Fan et al, 2018 ; Sun et al, 2020 ). It can respond to various biotic ( Mandal et al, 2018 ; Zhao et al, 2021 ) and abiotic ( Chen et al, 2017 ; Yao et al, 2020 ) stresses to resist the influence of environmental changes during plant growth and development. The immune response of melatonin in plants requires the participation of many signaling molecules, such as reactive oxygen species (ROS; Pardo-Hernández et al, 2020 ) and Nitric Oxide (NO; Zhu et al, 2019 ), to transmit both intracellular and intercellular signals.…”
Section: Introductionmentioning
confidence: 99%
“…The function of melatonin in plants has been widely reported ( Fan et al, 2018 ; Sun et al, 2020 ). It can respond to various biotic ( Mandal et al, 2018 ; Zhao et al, 2021 ) and abiotic ( Chen et al, 2017 ; Yao et al, 2020 ) stresses to resist the influence of environmental changes during plant growth and development. The immune response of melatonin in plants requires the participation of many signaling molecules, such as reactive oxygen species (ROS; Pardo-Hernández et al, 2020 ) and Nitric Oxide (NO; Zhu et al, 2019 ), to transmit both intracellular and intercellular signals.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, melatonin increased the activity of antioxidant enzymes, thus enhancing the tolerance of plants to high light. In addition, Yao et al (2020) reported the synthesis of melatonin was induced by UV-B. The wavelength of light spectrum also affected the synthesis of melatonin.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has previously been hypothesized to mediate plant responses through the constitutively overexpressed photomorphogenesis (COP)9 signalosome (Sanchez- Barcelo et al, 2016), an important mediator of ubiquitination and light-induced development or photomorphogenesis in plants. A recent in-depth study in Arabidopsis further supports this hypothesis showing that not only is the melatonin biosynthetic pathway upregulated and subsequently melatonin accumulated under UV-B exposure, but that melatonin mediated responses to UV-B exposure involves interactions with COP1 and the transcription factors HYH and HY5 (Yao et al, 2021). Though the mechanism is not well understood, the authors hypothesize that UV-B receptor 8 (UVR8), the UV-B receptor, binds to COP1 activating HY5 and HYH and their downstream gene regulation networks (Yao et al, 2021).…”
Section: Major Research Theme -Light Responsesmentioning
confidence: 77%
“…A recent in-depth study in Arabidopsis further supports this hypothesis showing that not only is the melatonin biosynthetic pathway upregulated and subsequently melatonin accumulated under UV-B exposure, but that melatonin mediated responses to UV-B exposure involves interactions with COP1 and the transcription factors HYH and HY5 (Yao et al, 2021). Though the mechanism is not well understood, the authors hypothesize that UV-B receptor 8 (UVR8), the UV-B receptor, binds to COP1 activating HY5 and HYH and their downstream gene regulation networks (Yao et al, 2021). It is unclear where in this pathway melatonin is acting, as both Arabidopsis cop1 and hy5 mutants show decreased responses to UV-B exposure, however, this is particularly interesting since the chromophore in the UVR8 receptor is a series of repeating tryptophan residues (Lee, 2016).…”
Section: Major Research Theme -Light Responsesmentioning
confidence: 77%